Multilocus phylogenetic analysis of the genus Atherina (Pisces: Atherinidae) - Francisco, Sara Martins (2012)
Sand-smelts are small fishes inhabiting inshore, brackish and freshwater environments and with a distribution in the eastern Atlantic and Mediterranean Sea, extending south into the Indian Ocean. Here, we present a broad phylogenetic analysis of the genus Atherina using three mitochondrial (control region, 12S and 16S) and two nuclear markers (rhodopsin and 2nd intron of S7). Phylogenetic analyses fully support the monophyly of the genus. Two anti-tropical clades were identified, separating the South African Atherina breviceps from the north-eastern Atlantic and Mediterranean Atherina’ species. In European waters, two groups were found. The first clade formed by a well supported species-pair: Atherina presbyter (eastern Atlantic) and Atherina hepsetus (Mediterranean), both living in marine waters; a second clade included Atherina boyeri (brackish and freshwater environments) and two independent lineages of marine punctated and non-punctated fishes, recently proposed as separate species. Sequence divergence values strongly suggest multiple species within the A. boyeri complex.